2018
DOI: 10.1177/1043454218810145
|View full text |Cite
|
Sign up to set email alerts
|

Returning to Social Life: Development of Social Identity for Adolescent and Young Adult Survivors of Leukemia in Korea

Abstract: The purpose of this study is to investigate the life experiences and processes that occur as adolescent and young adult leukemia survivors return to social life using grounded theory. Method: This study comprised 14 adolescents and young adults who visited a hospital for follow-up care after treatment of leukemia. We used in-depth interviews to examine the participants' experiences in returning to social life. The semistructured questionnaire examined "good and bad experiences in returning to social life," "so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Interventions that may improve meaning discovery include increasing social support, 98 legacy making through story or art, 100 increased benevolence toward others, 64 and certain meaning-centered programs. 101 Finally, there is evidence that fulfilling employment, meeting education goals, 102 and accomplishing tasks 103 may improve meaning discovery in patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions that may improve meaning discovery include increasing social support, 98 legacy making through story or art, 100 increased benevolence toward others, 64 and certain meaning-centered programs. 101 Finally, there is evidence that fulfilling employment, meeting education goals, 102 and accomplishing tasks 103 may improve meaning discovery in patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…No factors were found that decreased gratitude. The three predominant factors that increased gratitude were: having and surviving cancer, 55 , 57 , 148 peer support, 103 , 149 and a strong relationship with their health care provider. 110 , 150 Cancer was described as helping patients appreciate the small things in life.…”
Section: Resultsmentioning
confidence: 99%
“…The researchers reported that the people who have strong internal health locus of control (the belief that they can control their health condition) was likely to learn self-management [ 14 ] and showed high QOL [ 15 ], self-esteem, and life satisfaction [ 16 ]. The people having cancer showed lower scores of internal health locus of control than those of healthy people [ 17 ] because they continuously experienced a fear of recurrence [ 18 ]. However the sure way to prevent cancer recurrence is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…The subscales of IPQ are identity, cause, time‐line and control/cure; those of IMIQ are seriousness, personal responsibility, controllability and changeability; those of MIQ are impact of Activities of Daily Living (ADL), type of stress, degree of stress, positive attitude/control and expectancy/reoccurrence; although those of the ICQ focus on patient psychological response to illness: helplessness, acceptance and perceived benefits (Lauwerier et al, 2010; Maas et al, 2009). Because accepting chronic illness is a key factor of the social life of adolescents with chronic illness (An & Lee, 2019b; Im, Lee, Yun, & Choi, 2017), ICQ was considered a useful instrument to investigate the acceptance of Korean adolescents and how that acceptance accepts their social life.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study reported stronger concern about illness by Japanese patients than Dutch patients (Kaptein et al, 2013). Asian society is framed by Confucianism, which includes a strong belief of a standard life (An & Lee, 2019b). Korean adolescents are more likely to consider themselves different from their peer group (An & Lee, 2019a).…”
Section: Introductionmentioning
confidence: 99%